Go virtual: Exploring the potential of adaptive e-learning platform for dissemination of architectural knowledge - Abdullah, Fadzidah; Azmin, Aida Kesuma; Kassim, Mohd Hisyammudin; Sanusi, Aliyah Nur Zafirah (American Scientific Publishers, 2017)
Architectural education is considered unique in the sense that it is built on the principle of learning by doing, and associated with apprenticeship, where knowledge dissemination and skill development requires face to face interaction between learners and teachers. Hence, attempts at changing the established method would require thorough investigation especially on its impacts on architectural education. This requirement explains why while many disciplines have explored the e-learning environment; yet architectural education remains with its apprenticeship method despite the advance of current digital technologies. The objectives of the research are to examine the effectiveness and relevancy of i-Ta’leam as a platform for knowledge dissemination in architectural education. This research employs quantitative approach where survey questionnaires were distributed to architecture students to seek their opinions on their experience of using i-Ta’leam as their e-learning platform. Generally, albeit its relevancy, students gave negative feedbacks on the effectiveness of I-Ta’leem as an e-learning platform. Suggestions are given to enhance its functions and potential as an efficient interface for architectural education.